Efficacy and safety of palbociclib plus endocrine therapy in North American women with hormone receptor‐positive/human epidermal growth factor receptor 2‐negative metastatic breast cancer. Issue 3 (25th August 2019) - Gelmon, Karen A.; Cristofanilli, Massimo; Rugo, Hope S.; DeMichele, Angela M.; Joy, Anil A.; Castrellon, Aurelio; Sleckman, Bethany; Mori, Ave; Theall, Kathy Puyana; Lu, Dongrui R.; Huang, Xin; Bananis, Eustratios; et al.
Abstract: Palbociclib is a cyclin‐dependent kinase 4/6 inhibitor indicated for treatment of hormone receptor‐positive/human epidermal growth factor receptor 2‐negative advanced breast cancer in combination with endocrine therapy. We investigated the efficacy and safety of palbociclib in patients enrolled in North America during two‐phase 3 trials: PALOMA‐2 (n = 267, data cutoff: May 31, 2017) and PALOMA‐3 (n = 240, data cutoffs: April 13, 2018, for overall survival, October 23, 2015, for all other outcomes). In PALOMA‐2, treatment‐naïve postmenopausal patients with advanced breast cancer were randomized 2:1 to palbociclib (125 mg/d; 3 weeks on/1 week off [3/1]) plus letrozole (2.5 mg/d, continuous) or placebo plus letrozole. In PALOMA‐3, patients who progressed on prior endocrine therapy were randomized 2:1 to palbociclib (125 mg/d; 3/1) plus fulvestrant (500 mg, per standard of care) or placebo plus fulvestrant; pre/perimenopausal patients received ovarian suppression with goserelin. Palbociclib plus endocrine therapy prolonged median progression‐free survival vs placebo plus endocrine therapy in North American patients (PALOMA‐2: 25.4 vs 13.7 months, hazard ratio, 0.54 [95% CI, 0.40–0.74], P  < .0001; PALOMA‐3: 9.9 vs 3.5 months, hazard ratio, 0.52 [95% CI, 0.38–0.72], P  < .0001). Objective response and clinical benefit response rates were greater with palbociclib vs placebo in North American patients in both trials. While overall survival data are not yet mature for PALOMA‐2, median overall survival was increased in PALOMA‐3 (32.0 vs 24.7 months, hazard ratio, 0.75 [95% CI, 0.53–1.04]), though this did not reach statistical significance ( P  = .0869). Safety profiles in North American patients were similar to those of the overall populations; neutropenia was the most common treatment‐emergent adverse event. No new safety signals were observed. In summary, palbociclib plus endocrine therapy is an effective treatment option for North American women with hormone receptor–positive/human epidermal growth factor receptor 2–negative advanced breast cancer.